FITNESS RUNNING IN THE PROCESS OF PHYSICAL EDUCATION (Physical Culture and Sport: Scientific Perspective, 2024)
In today's world, where the pace of life is becoming more and more intense, the issues of maintaining health and physical activity are becoming especially relevant. Among the various forms of physical education, a personal place is occupied by fitness running, which is one of the most affordable and effective methods of maintaining health and physical fitness.Physical training of cadets is a pedagogically oriented process of providing specialized physical training for professional activities with specific characteristics. Physical education of cadets is an important component of the educational process in higher educational institutions of the Ministry of Internal Affairs system, aimed at forming a harmoniously developing personality capable of professional activity in conditions of high intensity of workload. Fitness running, as a part of physical education, contributes to the development of endurance, strengthening of the cardiovascular system, improvement of psycho-emotional state and general increase in the level of physical fitness of cadets.Fitness running is a specific means of training effect, which is difficult to replace with other physical activities. It is the simplest type of cyclic exercises. The article reveals the principles of organizing health running in the process of physical education. despite the obvious advantages of fitness running, the issue of its implementation in educational programs remains relevant. Research conducted in this field shows that regular concepts of running have a positive effect on the physical condition of cadets, however, methodological aspects and optimal conditions for the integration of recreational running into the educational process require further study. The purpose of this article is to analyze the effect of recreational running on the physical condition of cadets, to develop methodological recommendations for its introduction into the system of physical education, as well as to determine the optimal conditions for achieving the maximum recreational effect.Thus, the study of the role of fitness running in the physical education of cadets is a step on the way to increasing the effectiveness of physical training in the conditions of modern educational institutions, as well as the formation of a healthy lifestyle culture for the young generation.
Keywords: running; fitness running; health; cadets; physical education